KONTRIBUSI KELENTUKAN PINGGANG DAN EXPLOSIVE POWER OTOTTUNGKAI TERHADAP AKURASI SHOOTING ATLET SEPAK BOLA SMA N 3 BENGKULU SELATAN - M Taheri Akhbar (JURNAL PENDIDIKAN ROKANIA, 2017)
This study aims to determine contribution of flexibility waist and leg muscle power exsplosive to the shooting accuracy soccer athletes SMA N 3 South Bengkulu. This study uses correlation method where the data obtained from the field is transformed into numbers so do statistical calculations. The study population was a high school student N 3 South Bengkulu incorporated in extracurricular activities with the number of students 58 people. Samples were taken by using purposive sampling with a sampling of 25 people. Data collected by the waist with a flexibility test flexiometer tool, explosive power leg muscle premises standing broad jump test. And the accuracy of target shooting with a soccer test. The data collected was analyzed by correlation. The result showed that flexibility waist contributed 32,8% to shooting accuracy, leg muscle power exsplosive contributed 24,6% to shooting accuracy, flexibility waist and leg muscle power exsplosive contributed 57,4% to shooting accuracy